Isolation from Tobacco Mosaic Virus-Infected Tobacco of a Solubilized Template-Specific RNA-Dependent RNA Polymerase Containing a 126K/183K Protein Heterodimer - Watanabe, Takato (American Society for Microbiology, 1999)
The complete nucleotide sequence was determined for the putative RNA polymerase (183K protein) gene of tobacco mosaic virus (TMV) OM strain, which differed from the related strain, vulgare, by 51 positions in its nucleotide sequence and 6 residues in its amino acid sequence. Three segments of this 183K protein, each containing the sequence motif of methyltransferase (M), helicase (H), or RNA-dependent RNA polymerase (P), were expressed in Escherichia coli as fusion proteins with hexahistidine tags, and domain-specific antibodies were raised against purified His-tagged M and P polypeptides. By immunoaffinity purification, a template-specific RNA-dependent RNA polymerase containing a heterodimer of the full-length 183K and 126K (an amino-terminal-proximal portion of the 183K protein) viral proteins was isolated. We propose that the TMV RNA polymerase for minus-strand RNA synthesis is composed of one molecule each of the 183- and 126-kDa proteins, possibly together with two or more host proteins.